The Influence of Brand Equity Towards Consumer Purchase Decision of Starbucks (Case Study: Gen Z Starbucks Customer In Bandung) - Mohammad Luqman Fauzan Kamil; Teguh Widodo (Quantitative Economics and Management Studies, 2023)
One of the regular competitors for coffee shop owners is a coffee shop that has been around for a long time, namely Stabucks. This study aims to determine partially or simultaneously the effect of brand equity consisting of brand awareness, perceived quality, brand associations, and brand loyalty on purchase intention, and to determine how much influence brand equity has on purchase intention at Starbucks. coffee in Bandung city. Quantitative method used in this research. Purposive sampling was used in addition to non-probability sampling. Data collection in this study was carried out by distributing online questionnaires which were then filled out by respondents, and using theory and data from books and journals. 200 responses from Bandung are required to complete this survey. This study used the PLS-SEM data analysis. The research findings indicate that Brand Awareness, Brand Quality, and Brand Loyalty have an influence on Purchase Decisions. Therefore, it is recommended to maintain the Brand Equity held by Starbucks.